47‐2: Invited Paper: Highly Transparent AMOLED for Augmented Reality Applications. Issue 1 (30th May 2018) - Lin, Yu-Hsin; Chen, Peng-Yu; Chen, Kuo-Kuang; Jen, KR; Lu, Hsueh-Hsing; Liu, Chun-Hsin; Hong, Hong-Jye
Abstract : Augmented reality (AR) has started to become popular in our daily life, such as head up display, gaming, house decoration, and many other applications under exploration. Transparent AMOLED is regarded as one of best display technologies for AR applications. In this paper, a highly transparent 13 inch 100 PPI AMOLED was developed for this purpose. Through optimization of TFT array layer stack, OLED cathode pattern and encapsulation structure, 68% transmittance, low reflectance and low yellow index were achieved. With this highly transparent AMOLED, many AR applications can be realized in the future.